(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
The estimation of biomass in aquatic macroinvertebrates represents a tool for understanding part of the functioning of ecosystems and the dynamics of aquatic food webs. In this work, two methods were evaluated to obtain macroinvertebrate biomass under different types of preservation (preserved in ethanol or frozen), founding that frozen samples take longer to obtain a constant weight. Organisms that were sampled fresh, were frozen (-20°C, 24 hr) before weighing were used. In addition, organisms that were kept preserved in 70% ethanol for a period longer than six months, were used. All organisms were dried in an oven at 60°C and every 12 hr were weighed on a digital balance. Frozen specimens had a large weight loss within the first 36 hr. Then at 72 hr they reached a constant weight. Most of the organisms preserved in 70% ethanol had a weight loss during the first 24 hr and constant weights were reported from this same time. This study confirms that dry weight estimation of aquatic macroinvertebrates is affected by ethanol, reaching constant weights in a shorter time for frozen individuals.